Hypofractionated Stereotactic Ablative Radiotherapy for Recurrent or Oligometastatic Tumours in Children and Young Adults. Issue 5 (May 2020) - Chandy, E.; Taylor, H.; Gaito, S.; Wells, E.; Jones, C.; Meehan, C.; Burland, H.; Stone, J.; Snowball, C.; Mashru, J.; Riddell, C.; Hon, Y.; et al.
Abstract: Aims: Cancer remains a leading cause of death in children and adolescents in the developed world. Despite advances in oncological management, rates of primary treatment failure remain significant. Radiation of recurrent or metastatic disease improves survival in adults but there is little data to support clinical decision making in the paediatric/teenage and young adult population. Materials and methods: We present a retrospective case series of 14 patients treated with stereotactic ablative body radiotherapy or stereotactic radiosurgery at The Royal Marsden Hospital from September 2011 to December 2015. Eligible patients were aged <25 years, with Lansky/Karnofsky performance status ≥60 with confirmed relapsed or metastatic tumour in fewer than three sites. Follow-up was in accordance with standard clinical care and included regular outpatient review and radiological surveillance. Local control, progression-free survival and overall survival are presented. Results: Data for 14 patients with 18 treated lesions were included. The median patient age was 15 years (range 5–20 years). Nine patients were treated for local recurrence and five for metastatic lesions. All patients had already undergone multiple previous treatments. Eleven patients had undergone previous radiotherapy. The median interval between the completion of initial radiotherapy and reirradiation was 29.0 months (range 0.2–49.5 months). The median follow-up was 3.4 years (range 0.28–6.4 years). The 1-year local control rate was 78.6% and the 2-year local control rate was 57.1%. Overall median survival was 58.4 months (95% confidence interval 33.8–82.9 months). Cumulative biologically effective doses (BED) over 200 Gy were associated with late toxicity (P = 0.04). Conclusion: Radical doses of short-course hypofractionated radiotherapy can achieve excellent local control and may contribute to the prolongation of overall survival. There is a need for prospective trials exploring the use of ablative radiotherapy in metastatic disease in paediatric/teenage and young adult patients in order to establish safe and effective treatment schedules. Highlights: Stereotactic radiotherapy to sites of oligometastatic disease in children and young adults may prolong overall survival. Local control of oligometastases is 78.6% and 57.1.% at 1 and 2 years, respectively. Cumulative BED doses >200 Gy are associated with late toxicity.